Endoplasmic Reticulum Stress-Sensing Mechanism Is Activated in Entamoeba histolytica upon Treatment with Nitric Oxide - Santi-Rocca, Julien (Public Library of Science, 2012)
The Endoplasmic Reticulum stores calcium and is a site of protein synthesis and modification. Changes in ER homeostasis lead to stress responses with an activation of the unfolded protein response (UPR). The Entamoeba histolytica endomembrane system is simple compared to those of higher eukaryotes, as a canonical ER is not observed. During amoebiasis, an infection of the human intestine and liver by E. histolytica, nitric oxide (NO) triggers an apoptotic-like event preceded by an impairment of energy production and a loss of important parasite pathogenic features. We address the question of how this ancient eukaryote responds to stress induced by immune components (i.e. NO) and whether stress leads to ER changes and subsequently to an UPR. Gene expression analysis suggested that NO triggers stress responses marked by (i) dramatic up-regulation of hsp genes although a bona fide UPR is absent; (ii) induction of DNA repair and redox gene expression and iii) up-regulation of glycolysis-related gene expression. Enzymology approaches demonstrate that NO directly inhibits glycolysis and enhance cysteine synthase activity. Using live imaging and confocal microscopy we found that NO dramatically provokes extensive ER fragmentation. ER fission in E. histolytica appears as a protective response against stress, as it has been recently proposed for neuron self-defense during neurologic disorders. Chronic ER stress is also involved in metabolic diseases including diabetes, where NO production reduces ER calcium levels and activates cell death. Our data highlighted unique cellular responses of interest to understand the mechanisms of parasite death during amoebiasis.